Action of auxins, boron and harvest season on the rooting of kiwi fruit stem cuttings (Actinidia chinensis Pl cv Monty) - Ono, E. O.; Rodrigues, J. D.; dePinho, S. Z. (Fundacion Romulo Raggio, 1997)
Action of auxins on the rooting of stem cuttings of kiwi (Actinidia chinensis P. cv Monty). This work studies the effects of some synthetic auxins and B in the rooting of kiwi (Actinidia chinensis Planch cv Monty) stem cuttings. The treatments used were as follows: T1 (H2O); T2 (NAA 300 ppm); T3 (IBA 300 ppm); T4 (NAA 300 ppm + B); T5 (IBA 300 ppm + B); T6 (NAA 0,5%-talc) and T7 (IBA 0,5%-talc), applied to the bases of the cuttings. These were then placed in rooting dishes with pure vermiculite in a misty nebulization chamber until collection day (120 days). The evaluation of auxin and boric acid effects on kiwi stem cuttings were made based on the following observations: 1. The percentage of rooted stem cuttings; 2. reducing sugars and total sugar analyses (in g/100 g of dry matter); and 3. tryptophan analyses (in mu g/100 mg of dry matter). The results show that summer is the best season for rooting Actinidia chinensis Planch cv Monty stem cuttings. The use of IBA talc 0,5% on the bases of the cuttings shamed positive results too.
Keywords: Actinidia chinensis; stem cuttings; rooting; IBA; NAA; boron